Graphene-TiO2 Nanocomposite Photoanode Based on Quantum Dot Solar Cells - Yalcin, Mesut; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2017)
Quantum dot sensitized solar cells (QDSSCs) have attracted significant attention as promising third generation photovoltaic devices. Among all the QDSSCs cadmium (Cd) chalcogenide based QDSSCs have gained a significant interest due to their easy fabrication. In this study graphene-TiO2 nanocomposite photoanode was fabricated to obtained a negative capacitance. Negatronic devices based on quantum dot solar cell. The graphene-TiO2 composite was prepared by one step hydrothermal approach. CdS quantum dots were coated on nanocomposite photoanodes by successive ionic layer adsorption and reaction method. The junction characteristic QDSSCs was studied using current-voltage, capacitance-voltage and photocapacitance-time measurements. The result show that the CdS QDSSC graphene-TiO2 photoanode demonstrates a maximum power conversion efficiency of 0.245%, compared with a QDSSC based on pure TiO2 photoanode (0,086%). The performance improvement is ascribed to the increased CdS absorbtion, reduction of electron recombination. Also the electron transfer is increased with the incorporation of graphene. The capacitance-voltage characteristic was measured in a wide frequency range of 50 kHz-1 MHz for QDSSC at room temperature. The capacitance-voltage characteristic shows a behavior from the positive to negative capacitance due to injection of electrons from the FTO electrode into TiO2.
Keywords: Solar Cells; Graphene; QDSSC; Quantum Dots; Nanocomposite; Negative Capacitance